PERANCANGAN SISTEM DIGITAL SIGNAGE SEBAGAI PAPAN INFORMASI TERKAIT PROTOKOL KESEHATAN DAN DATA UP TO DATE COVID-19 DI MASJID AL-IRSYAD JAKARTA - Rifqi Putra Riswarta; Nifty Fath (FAKULTAS TEKNIK UNIVERSITAS BUDI LUHUR, 2021)
During the Covid-19 pandemic, places of worship have the potential to become clusters for spreading the virus. It is necessary to have a digital information board related to health protocols and up to date data on Covid-19 installed in places of worship so that people can always be alert and obedient to implementing health protocols. Therefore, in this research, a digital signage has been designed using a raspberry pi microcontroller and a pisignage platform. This digital signage server uses web hosting from Pisignage to manage connected clients, make changes to the content displayed and can be accessed using smartphones and laptops. The digital signage client uses a raspberry pi connected to an LED TV to display the information sent by the server. Based on the results of the design, the display of information on each client is as planned. All information on the spread of covid-19 and image and video content can be seen and displayed on the digital signage client up to date. Based on the test results, this system has very good performance when using LAN and WLAN transmission media according to the TIPHON standard with an index value of 4. Based on the results of QoS analysis according to ITU-T G.1010 the comparison between image content and video content using wi-fi networks is obtained The conclusion is that the Qos parameter value of image content is smaller than video content due to different data sizes and bandwidths.